Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557230
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic difficulty using brain metrics of workload

Abstract: Dynamic difficulty adjustments can be used in humancomputer systems in order to improve user engagement and performance. In this paper, we use functional near-infrared spectroscopy (fNIRS) to obtain passive brain sensing data and detect extended periods of boredom or overload. From these physiological signals, we can adapt a simulation in order to optimize workload in real-time, which allows the system to better fit the task to the user from moment to moment. To demonstrate this idea, we ran a laboratory study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 39 publications
0
69
0
Order By: Relevance
“…Afergan et al [1] demonstrated the ability to distinguish between different workload states (Sensitivity) during a UAV simulation task. Additionally, the study identified workload changes over time (Bandwidth).…”
Section: Reliability Of Fnirsmentioning
confidence: 99%
“…Afergan et al [1] demonstrated the ability to distinguish between different workload states (Sensitivity) during a UAV simulation task. Additionally, the study identified workload changes over time (Bandwidth).…”
Section: Reliability Of Fnirsmentioning
confidence: 99%
“…For example, Csíkszentmihályi (1975) introduced "flow" as a key concept in performance motivation. The flow mental state means a zone in which the user intrinsically performs an action in a feeling of energized focus and full attentional involvement that leads to a moderate level of mental effort (Afergan et al, 2014). Because of the positive relationship between intrinsic motivation and mental effort, pupillometry researchers have found that pupils enlarge when people view interesting stimuli.…”
Section: Limitationsmentioning
confidence: 99%
“…GSR data were also tested by the Boosting algorith m with Haar-like features for cognitive load classifications . Furthermo re, Afergan et al [7] used functional near-infrared spectroscopy (fNIRS) to detect task difficulty and optimize workload with a dynamic adaptation. Ho wever, few research es use GSR features to index cognitive load dynamically in an adaptive feedback loop.…”
Section: Related Workmentioning
confidence: 99%